A Medieval Critique of Anthropomorphism : Ibn al-Jawzī's - Swartz, Merlin (Brill Book Archive Part 1, ISBN: 9789004472495., 2002)
This study consists of a critical edition of Ibn al-Jawzī's Kitāb Akhbār as-Sifāt (KAS) along with an annotated translation and introduction. KAS is a critique of anthropomorphic conceptions of God, directed in the first instance against Ibn al-Jawzī's fellow Hanbalī, but also against Sunnī traditionalists more generally. As an intra-Hanbalīr polemic, KAS sheds important new light on the intellectual fault-lines within medieval Hanbalism, and reveals the extent to which kalām had penetrated the Hanbalite school by the 12th century. In his work, Ibn al- Jawzī's makes extensive use of kalām , drawing on its technical language and crafting his arguments against anthropomorphism on the basis of the dialectical methods developed within the great theological schools of medieval Islam. The study also contains a translation of al-ʿAlthī's Risāla , a pointed response to Ibn al-Jawzī, written by a fellow Hanbalī from a traditionalist perspective.